LncRNA MCM3AP-AS1 Upregulates CDK4 by Sponging miR-545 to Suppress G1 Arrest in Colorectal Cancer - Ma X; Luo J; Zhang Y; Sun D; Lin Y (Cancer Management and Research, 2020)
Xudong Ma,1 Jing Luo,1 Yi Zhang,2 Dali Sun,1 Yueying Lin1 1Gastrointestinal Surgery, The Second Affiliated Hospital of Kunming Medical University, Kunming City, Yunnan Province 650031, People’s Republic of China; 2The General Surgery Department, The Teng-Chong People’s Hospital, Tengchong City, Yunan Province, 679100, People’s Republic of ChinaCorrespondence: Yueying Lin Email us5010@163.comIntroduction: This study aimed to investigate the role of lncRNA MCM3AP-AS1 in colorectal cancer (CRC).Methods: Paired tumor and non-tumor tissues were collected from 60 CRC patients. Expression of MCM3AP-AS1 was determined by RT-qPCR. Overexpression of MCM3AP-AS1, miR-545, and CDK4 in CRC cells was achieved to explore the interactions between them. Cell cycle assay was performed to analyze the roles of MCM3AP-AS1, miR-545, and CDK4 in regulating the cell cycle progression of CRC cells.Results: We found that MCM3AP-AS1 was upregulated in CRC and its high expression levels predicted poor survival of CRC patients. MCM3AP-AS1 is predicted to interact with miR-545. In CRC cells, overexpression of MCM3AP-AS1 and miR-545 was achieved, while their overexpression did not affect the expression of each other. Instead, overexpression of MCM3AP-AS1 led to the increased expression levels of CDK4, which is a downstream target of miR-545. Cell cycle analysis showed that overexpression of MCM3AP-AS1 and CDK4 suppressed G1 arrest induced by miR-545. In addition, overexpression of MCM3AP-AS1 reduced the enhancing effects of overexpressing miR-545 on cell cycle progression.Conclusion: MCM3AP-AS1 may upregulate CDK4 by sponging miR-545 to induce G1 arrest in CRC cells.Keywords: MCM3AP-AS1, colorectal cancer, miR-545, CDK4, G1 arrest